A systematic review of recent developments in disaster waste management - Zhang, Fanshun; Cao, Cejun; Li, Congdong; Liu, Yang; Huisingh, Donald (Journal of cleaner production, 2019)
Disaster waste management received increasing attention in recent years, but there was no review updating the evolving development after the study of Brown et al. (2011a). To explore how the topics in disaster waste management evolved in recent years and to analyze whether the gaps identified by Brown et al. (2011a) are covered, 82 papers published from 2011 to 2019 were selected from the Scopus database based on the defined process and criteria. This paper systematically examines the disaster waste management research from nine aspects of planning, waste, waste treatment options, environment, economics, social considerations, organizational aspects, legal frameworks and funding. The results suggested that there were no obvious changes or developments in the field of disaster waste management, although a few research gaps have been addressed, such as waste separation, waste quantities, case studies of incineration and waste to energy, direct economic effects, social considerations as well as application of GIS technology. Except for the comparative studies, future directions were suggested by the gaps that persist since Brown et al. (2011a) and the new gaps that were identified in this review. •A systematic review was done to review recent advances in disaster waste management.•There were no dramatic new developments in the field of disaster waste management.•Recent studies mainly focus upon technical aspects.•Planning, legislation, organizations and funding were not well addressed.•Future research directions are proposed.